Oil price shocks, monetary policy and current account imbalances within a currency union - Timo Baas; Ansgar Belke (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
For more than two decades now, current-account imbalances are a crucial issue in the international policy debate as they threaten the stability of the world economy. More recently, the government debt crisis of the European Union shows that internal current account imbalances inside a currency union may also add to these risks. Oil price fluctuations and a contracting monetary policy that reacts on oil prices, previously discussed to affect the current account may also be a threat to the currency union by changing internal imbalances. Therefore, in this paper, we analyze the impact of oil price shocks on current account imbalances within a currency union. Differences in institutions, especially labor market institutions and trade result in an asymmetric reaction to an otherwise symmetric shock. In this context, we show that oil price shocks can have a long-lasting impact on internal balances, as the exchange rate adjustment mechanism is not available. The common monetary policy authority, however, can reduce such effects by specifying an optimum monetary policy target. Nevertheless, we also show that there is no single best solution. CPI, core CPI or an asymmetric CPI target all come at a cost either regarding an increase in unemployment or increasing imbalances. – – Seit mehr als zwei Jahrzehnten sind Leistungsbilanzungleichgewichte ein zentrales Thema in der internationalen politischen Debatte, da sie die Stabilität der Weltwirtschaft bedrohen. In jüngerer Zeit demonstrierte die europäische Staatsschulden- und Bankenkrise, dass interne Leistungsbilanzungleichgewichte innerhalb einer Währungsunion diese Risiken noch verstärken können. Ölpreisschwankungen und eine auf den Ölpreis reagierende, zunehmend kontraktive Geldpolitik, können auch eine Bedrohung für die Währungsunion darstellen, da sich durch sie auch die unions-internen Ungleichgewichte ändern. Daher analysieren wir in diesem Papier die Auswirkungen von Ölpreisschocks auf Leistungsbilanzungleichgewichte innerhalb einer Währungsunion. Unterschiede in Institutionen, insbesondere in Arbeitsmarktinstitutionen, und im Handel führen zu einer asymmetrischen Reaktion auf einen ansonsten symmetrischen Schock. In diesem Zusammenhang zeigen wir, dass Ölpreisschocks langfristige Auswirkungen auf die internen Leistungsbilanzsalden haben können, da der Wechselkursanpassungsmechanismus in der Währungsunion nicht verfügbar ist. Die zentrale monetäre Instanz der Währungsunion kann diese Effekte jedoch durch Festlegung eines optimalen geldpolitischen Ziels reduzieren. Wir zeigen aber auch, dass es keine einzelne beste Lösung gibt. Die Verbraucherpreisinflation, die Kern-Verbraucherpreisinflation oder ein asymmetrisches Inflationsziel haben alle ihren Preis, entweder im Hinblick auf eine Zunahme der Arbeitslosigkeit oder zunehmende Ungleichgewichte.
Keywords: E32; F32; F45; Q43; 330; current account deficit; oil price shocks; DSGE models; search and matching labor market; monetary policy